Ferritin heavy chain mediates the protective effect of heme oxygenase-1 against oxidative stress - Cheng, Hui-Teng; Yen, Chung-Jen; Chang, Chen-Chih; Huang, Kuo-Tong; Chen, Kuo-Hsuan; Zhang, Rui-Yang; Lee, Ping-Yi; Miaw, Shi-Chuen; Huang, Jenq-Wen; Chiang, Chih-Kang; Wu, Kwan-Dun; Hung, Kuan-Yu (Biochimica et biophysica acta, 2015)
The phenomenon that heme oxygenase-1 (HO-1) protects cell from injury yet its enzymatic product, iron, may facilitate generation of free radical has been long puzzling. Here we establish a functional connection between ferritin heavy chain (FHC) and HO-1. In human lupus nephritis HO-1 and FHC are colocalized within the glomeruli. In rodent anti-Thy1 (thymocyte antigen 1) induced glomerulonephritis, heme oxygenase blockade lowers the expression of FHC and accelerates mesangial cell death. Stimulation of heme oxygenase in cultured rat mesangial cell enhances its resistance to hydrogen peroxide, whereas FHC knockdown by RNA interference compromises this salutary effect. RNA interference of HO-1 makes the cell more susceptible to hydrogen peroxide, which can be rescued by forced expression of wild-type FHC but not mutants that lose the capacity of iron storage and ferroxidase activity. Phosphorylation of JunD was not sustained in these cells. Microarray analysis identifies four candidate transcriptional factors that may regulate the HO-1-induced transcription of FHC. Our results support the role of FHC in neutralizing the iron toxicity as well as mediating the protective effect of HO-1 in response to oxidative stress. •HO-1 is colocalized with FHC and C4d within the glomeruli in human lupus nephritis.•Inhibition of HO activity lowers FHC expression in anti-Thy1 glomerulonephritis in rats.•Deficiency of HO-1 results in lower JunD phosphorylation and transcription of FHC, Lyl1, Rybp, Ppp1r10, and Tef.•FHC mediates the cytoprotective effect of HO-1 via iron storage capacity and/or ferroxidase activity.